A Combination of CPI-0610 and SAHA Induces Apoptosis through STAT3 and p38 Signalling Pathways in Diffuse Large B-cell Lymphoma Cells - Xu, Linyan; Jiao, Jun; Liu, Mengdi; Qin, Yuanyuan; Zhang, Meng; Yan, Dongmei; Xu, Kailin; Sang, Wei (Current Medicinal Chemistry, 2025)
BackgroundAlthough immunotherapies have greatly improved diffuse large B-cell lymphoma (DLBCL) prognosis, a proportion of patients remain to be relapsed or refractory. Therefore, the identification of novel therapeutic targets and drugs is urgently required. Inhibition of the bromodomain and extra-terminal (BET) proteins has been a promising therapeutic strategy for various haematologic cancers. CPI-0610 is a potent and selective BET inhibitor. The effects of CPI-0610 in DLBCL cells have not been reported yet.AimsThe aim of this study was to assess the effects of CPI-0610 in DLBCL and its underlying mechanisms.MethodsDLBCL cells were treated with CPI-0610, followed by measuring cell viability, cell cycle, apoptosis, autophagy, and specific cell signaling pathways. Moreover, immunodeficient mice were engrafted with SUDHL2 cells and then treated with CPI-0610 for analysis of tumor burden. We also analyzed the synergistic effect of CPI-0610 with histone deacetylase inhibitor suberoylanilide hydroxamic acid.ResultsThe present study demonstrated that CPI-0610 displayed cell cytotoxicity by arresting the G1 cell cycle and inducing endogenous and exogenous apoptotic pathways. Additionally, CPI-0610 decreased BRD4 and c-Myc expressions and affected MAPK, JAK/STAT, and AKT signalling pathways in human DLBCL cells. An in vivo experiment exhibited that CPI-0610 decreased the primary tumour growth of the DLBCL xenograft model. Furthermore, the use of CPI-0610 in combination with suberoylanilide hydroxamic acid exhibited a specific synergistic effect in inducing apoptosis through the regulation of STAT3 and p38.ConclusionTargeting BET may be an effective therapeutic strategy and potentiated by a combination with histone deacetylase inhibition in DLBCL.
Keywords: STAT3